Pengaruh Upah Minimum, Kemiskinan dan Pengangguran pada IPM di Kabupaten/Kota Provinsi Jawa Timur - Faizin, Moh. (Fakultas Ekonomi Universitas Samudra, 2021)
The paradigm of development of a country today is not only measured by the rate of economic growth, but also by paying attention to human development. The purpose of this study was to analyze the effect of minimum wages, poverty and unemployment on the Human Development Index (HDI) in districts/cities in East Java Province. The method used is panel data regression in 38 districts/cities in East Java in 2010/2018. The results showed partially, the minimum wage has a positive and significant effect, poverty has a negative but not significant effect, and unemployment has a negative and significant effect, toward HDI. Simultaneously, the results found that the three independent variables (i.e.: minimum wage, poverty and unemployment) had a significant effect on HDI.